2015
DOI: 10.2478/jee-2014-0063
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Conacts to p-GaN on the Basis of Carbon Nanomaterials

Abstract: We have designed and verified a new structure for ohmic contacts to p-GaN based on a layer of carbon nanotubes (CNT), reduced graphene oxide (r-GO) and metallic layers of Cr, Pd and Au, namely in configurations Au/Cr/r-GO/CNT/p-GaN and Au/Pd/r-GO/CNT/p-GaN. The effects have been studied of the annealing temperature and the gas ambient upon the electrical properties of the contacts. Annealing of the Au/Pd/r-GO/CNT/p-GaN structure in air at 500 • C for 1 minute resulted in linear I − V curves measured between pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…17 Recently, Liday et al have demonstrated low resistance contacts by using CNT/r-GO/CNT on p-type GaN. 18 Typically, a Schottky contact PD is used for self-powered applications.…”
mentioning
confidence: 99%
“…17 Recently, Liday et al have demonstrated low resistance contacts by using CNT/r-GO/CNT on p-type GaN. 18 Typically, a Schottky contact PD is used for self-powered applications.…”
mentioning
confidence: 99%